Peran Pemuda Desa dalam Melestarikan Tradisi Berejung pada Suku Rejang di Desa Pasar Kerkap Kecamatan Air Napal Kabupaten Bengkulu Utara - Putri Analya, Martsyah (IJOCE: Indonesia Journal of Civic Education, 2026)
This study aims to find the role of youth in preserving the Berejung tradition of the Rejang tribe in Pasar Kerkap Village, Air Napal District, North Bengkulu Regency, as well as the supporting and inhibiting factors using observation, interview, and documentation methods. The results of the study indicate that the role of youth in preserving the Berejung tradition is very lacking, due to the indifferent nature of the younger generation in knowing and learning Berejung and the lack of role of youth and the community itself. Supporting factors for youth in preserving the Berejung tradition in this study are the existence of facilities and infrastructure such as the Risma group as a forum for developing Berejung preservation, guitar as a modern musical instrument to accompany Berejung, and the existence of the Village Hall as a training place. Inhibiting factors for youth in preserving the Berejung tradition are the lack of interest of the younger generation, lack of knowledge about the Berejung tradition, and acculturation of developments from globalization. In conclusion, the role of youth in preserving the Berejung tradition is very lacking, due to the indifferent nature of the younger generation in knowing and learning Berejung and the lack of role of youth and the community itself.   Keywords: Role of Youth, Tradition, Rejang Tribe, Berejung